2018
DOI: 10.3389/fbioe.2018.00113
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Toll-Like Receptor 2 and 4 Innate Immunity Pathways in Intracortical Microelectrode-Induced Neuroinflammation

Abstract: We have recently demonstrated that partial inhibition of the cluster of differentiation 14 (CD14) innate immunity co-receptor pathway improves the long-term performance of intracortical microelectrodes better than complete inhibition. We hypothesized that partial activation of the CD14 pathway was critical to a neuroprotective response to the injury associated with initial and sustained device implantation. Therefore, here we investigated the role of two innate immunity receptors that closely interact with CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 79 publications
(130 reference statements)
0
20
0
Order By: Relevance
“…In this study, TLR2 and TLR4 both remained upregulated following injury, while DUSP1’s regulation remained suppressed, suggesting the ongoing traffic of inflammatory factors post-implantation through TLRs (Figure 3B). Of the two TLRs studied, TLR4 was recently shown to affect intracortical electrode functionality, decreasing its performance [158]. Both inflammatory secretion and TLR activation imply a continuation of inflammatory signaling at low but persistently upregulated values by 7-day, which may result in chronic inflammation deteriorative to the local brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TLR2 and TLR4 both remained upregulated following injury, while DUSP1’s regulation remained suppressed, suggesting the ongoing traffic of inflammatory factors post-implantation through TLRs (Figure 3B). Of the two TLRs studied, TLR4 was recently shown to affect intracortical electrode functionality, decreasing its performance [158]. Both inflammatory secretion and TLR activation imply a continuation of inflammatory signaling at low but persistently upregulated values by 7-day, which may result in chronic inflammation deteriorative to the local brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…The former is the “classical activation” phenotype, in which cells secrets pro-inflammatory cytokines and contribute to neuronal injury; in the case of the latter phenotype cells secret anti-inflammatory cytokines and contribute to tissue remodeling and repair, phagocytosis of cell debris, as well as antagonize pro-inflammatory activity. In the early hours post-implantation, pro-inflammatory microglia secrete pro-inflammatory cytokines and chemokines such as interleukins IL-1α, IL-1β, IL-6, tumor necrosis factor (TNF-α), monocyte chemoattractant protein 1 (MCP-1) (Sawyer et al, 2014), ROS and reactive nitrogen species (RNS), determining massive immune cell recruitment and additional cytokine production (Hermann et al, 2018a). The lack of oxygen redox homeostasis acts directly on microglia, astroglia and endothelial cells causing activation of metalloproteinase, downregulation of tight junctions and adherens junction genes in the first hours after BBB injury (Bennett et al, 2018), facilitating the entrance of infiltrating macrophages, which will also have a crucial role in neurodegeneration (Ravikumar et al, 2014).…”
Section: Foreign Body Response As a Cause Of Implant Failurementioning
confidence: 99%
“…Genetically engineered animal models are another successful tool in microelectrode research. Mice lacking specific genes involved in neuroinflammation and immunity were employed to investigate the biochemical pathways involved in the foreign body response, the identification of pharmacological targets (Kozai et al, 2014; Bedell et al, 2018b; Hermann et al, 2018a,b) and material testing (Lee et al, 2017). Mice carrying cell specific fluorescent tags have been shown to provide great advantages in the study of the contribution of different cells in a single animal as well as a valuable alternative to immunostaining steps (Sunshine et al, 2018; Eles et al, 2019).…”
Section: Experimental Models To Study Foreign Body Response To Neuralmentioning
confidence: 99%
“…Studies with TLR2/TLR4 utilized dummy implants and investigated only the histological response. 229 Endpoint histology at 2 and 16 weeks after implantation demonstrated that Tlr4 −/− mice exhibited significantly lower BBB permeability at acute and chronic time points but also demonstrated significantly lower neuronal survival at the chronic time point. Additionally, inhibition of the TLR2 pathway had no significant histological effect compared to control animals.…”
Section: Discussionmentioning
confidence: 94%